Animal welfare in free-range systems: Integrating environmental, behavioral, and physiological aspects in Lohmann Brown egg-laying hens (Research, Society and Development, 2025)
The free-range system has been used as an alternative to promote the welfare of laying hens. This study aimed to evaluate the environmental and behavioral factors of laying hens raised in this system. Conducted in a commercial barn, the study involved hens aged 18-24 weeks from the Lohmann-Brown lineage. The microclimate, aviary bedding, and nests were assessed, along with pododermatitis and feather condition. Measurements of temperature, respiratory frequency, and corticosterone hormone analysis were also conducted. The climatic conditions were favorable, remaining within the thermoneutral zone, with no incidence of pododermatitis or feather lesions. Natural, social, feeding, reproductive, stress-related, locomotor, exploratory, and resting behaviors were observed, with morning highlighting internal area and afternoon external area. Maintenance behaviors prevailed in the afternoon, with greater social behavioral expression in the intermediate period. The interaction between observation period and age of the hens had a significant effect on body temperature. Behavioral and physiological assessments are effective tools for evaluating animal welfare. It is concluded that the free-range system is satisfactory in terms of comfort and welfare of laying hens.